WINNING SOULS IN THE DIGITAL ERA: CHURCH MISSIOLOGY STRATEGIES IN DIGITAL TRANSFORMATION - Jontha Fresly (Social Studies and Humanities Journal (SOSHUM), 2025)
This study explores the transformation of the concept of soul-winning in the context of the church's digital missiology in the era of digital transformation. Using a narrative review approach, this study examines the literature on mission theology, digital communication, and the sociology of religion to identify the changing paradigm of Christian mission. The results show that the mission paradigm is shifting from individual conversion to a relational and community approach, where the digital space becomes a strategic arena for participation in Missio Dei. The concepts of digital incarnation and ecclesia digitalis emphasize that the presence of faith in cyberspace is an authentic expression of Christian ministry. This study also identifies challenges such as depersonalization, shallow interactions, and issues of spiritual authority, as well as opportunities to reach digital-native generations and non-traditional contexts. The proposed Digital Missiology Framework provides a theological, strategic, and ethical conceptual framework for churches to develop digital ministries that are transformative and relevant to digital culture.